A security services for internet of thing smart health care solutions based blockchain technology - Ahmed Hashim Mohammed; Rawaa Mohammed Abdul Hussein (Universitas Ahmad Dahlan, 2022)
Pervasive and ubiquitous computing has enabled people better integrate physical things into the digital world. The internet of things (IoT) has been considerably more widely used in business and everyday life in the last decade. Innovative healthcare information and communication technologies are a vast field of research and applications that need IoT benefits, including speed, security, and low cost. The proposed modified advanced encryption standard (AES)-cipher block chaining (CBC)-based blockchain technology offers a shared key to devices that need to communicate directly with or with entities outside the smart healthcare network to give users greater control over transactions. The experiments are carried out using a Raspberry Pi 3, whereas two different sensors are ‎employed in this case. Blockchain technology encrypts data between doctor and patient with varied user numbers. The results from experiments revealed that the proposed modified AES-CBC based blockchain technology could provide the IoT application with security services (confidentiality, integrity, and access control) with efficient execution time.